2006
DOI: 10.1016/j.jcrysgro.2006.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Growth of InN by vertical flow MOVPE

Abstract: InN films were grown by metal-organic vapour phase epitaxy (MOVPE). The growth was performed in a MOVPE apparatus with a vertical reactor geometry optimized for the growth of GaN. The reactor geometry is found to cause enhanced cracking of NH 3 , and the growth rate is limited by the amount of reactive indium in the temperature range of 550-650 1C. The grown films are characterized comprehensively. Experimental results indicate that the InN films, grown on sapphire substrates, contain metallic indium and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 17 publications
7
33
0
Order By: Relevance
“…But with further increased temperature, In droplets could be observed again. This has been attributes to N desorption at this high temperature, leaving metallic In on the surface [5].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…But with further increased temperature, In droplets could be observed again. This has been attributes to N desorption at this high temperature, leaving metallic In on the surface [5].…”
Section: Resultsmentioning
confidence: 92%
“…They reported that increasing growth temperature roughened the surface and broadened the full-width at half maximum (FWHM) of XRC scans but also observed a decreasing carrier concentration. The effect of V/III ratio was studied by Suihkonen et al [5], they reported that the growth rate is not limited by the TMIn flow but reactive N in the reactor, a lack of which also leads to In droplet formation. in this paper, the effect of main growth parameters like temperature, pressure and V/III ratio on InN growth and droplet formation has been investigated precisely and the quality of MOCVD-grown InN films has been improved regarding their crystalline and electrical properties.…”
mentioning
confidence: 99%
“…High-quality InN has been grown mainly by molecular beam epitaxy (MBE) [3][4][5][6] and metalorganic vapor phase epitaxy (MOVPE) [7][8][9]. The optimal substrate temperature (T s ) for InN growth is close to the decomposition temperature of the material, around 500°C [10].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk material is not available, but high quality films on sapphire ͑either directly or using various buffer layers͒ have been fabricated by molecular beam epitaxy ͑MBE͒ [1][2][3][4] and also by metal-organic chemical vapor deposition ͑MOCVD͒. 5,6 The properties of the material are greatly affected by the layer thickness and substrate material, as well as the growth temperature and stoichiometry. In this work, we apply positron annihilation spectroscopy to study the effect of different growth conditions, i.e., growth temperature, polarity and stoichiometry, film thickness, and substrate material on vacancy formation in InN grown by MBE.…”
mentioning
confidence: 99%